Darwin: Towards the sustainability of the Larrikin of Australian capital cities. (January 2022) - Kavaarpuo, Godwin; Oppong-Yeboah, Nana Yaw; Vuin, Ana
Abstract: Cities, as entities, are inevitably exposed to a range of the internal and external factors that shape their urban development and planning. As complex adaptive systems, cities possess different capabilities and opportunities for the re-configuration, transformation and learning from these disturbances. This city profile explores these processes using Darwin, the Northern Territory's capital and Australia's eighth-largest city as an example. The city profile is situated within Urban Resilience Theory. It unpacks the nuanced way geographic factors and spatial isolation; natural disasters, World War 2 bombing, border security threats, natural resource extraction, and tourism have shaped Darwin's urban development. Understanding these nuances and their spatiotemporal dynamics coalesces into the identified system susceptibilities and opportunities for an adaptive and sustainable development presented in this paper. The city's unique urban governance, successive reconstruction, socio-spatial dynamics, history, and challenges make it an excellent case study of city growth dynamics and resilience within the Asian-Pacific region. The profile highlights Darwin's regional planning and the (historic) production of urban space, along with climate change risks and adaptation, increasingly inaccessible housing and unaffordability, economic growth challenges and demographic dynamics. Highlights: Population growth was associated with capital projects, resource extraction booms, and military presence in Darwin. Complex political, socio-economic, and disruptive forces shaped population growth, urban planning, and development. Darwin has one of the most expensive rental housing markets among Australian capital cities. Current spatial growth and development furthered automobile-dependent mobility among households. Project-based development approaches proved to be inadequate to deliver sustainable and resilient urban development.